Peran Produser Dalam Pembuatan Program Feature Kuliner “Rasa Nusantara” Edisi Warung MJS - Anggrid Putri Dewi; Muhammad Darwinsyah (Lembaga Pengembangan Kinerja Dosen, 2024)
With the decreasing popularity of typical Indonesian food, television must develop more creativity in Indonesian culinary feature programs, therefore the role of television media is needed which can present information about culinary with interesting concepts and also present a variety of dishes from various regions in Indonesia. The creator of the work created a culinary feature program that has a lot of information and is also a reference for unique and interesting places to eat or restaurants with the theme of typical Indonesian food as inspiration and is also suitable for generation Z to get to know and preserve the culinary riches of the archipelago. The creator created a culinary feature program